Congenital Aberrant Tearing: A Re-Look - Miller, Marilyn T. (The American Ophthalmological Society, 2008)
PURPOSE: Congenital aberrant tearing is characterized by tearing when eating (“crocodile tears”), lack of emotional tearing, or both. Most reported cases are associated with Duane syndrome. In our previous studies we observed aberrant tearing in individuals with thalidomide embryopathy and Möbius sequence. This report summarizes the literature on the subject and adds 3 new studies that give information on this unusual condition. METHODS: Twenty-eight individuals with Möbius sequence were interviewed about tearing symptoms at a support group meeting in Italy. In Sweden 30 adults primarily from the original thalidomide series were reexamined. In this latter study, a Schirmer test was done at baseline and repeated 5 minutes after eating. Twenty families in Brazil who have children with Möbius sequence were questioned about tearing symptoms and exposure to misoprostol during pregnancy. RESULTS: In the 28 Italian individuals, either “crocodile tears” or lack of emotional tearing was noted in 7 cases. In the thalidomide study, 10 of 30 patients had tearing when eating and 7 had no emotional tearing. Low Schirmer scores or increased tearing after eating was noted in a few asymptomatic individuals. Among the 20 Brazilian children with Möbius sequence, 10 had some tearing abnormality. CONCLUSION: Congenital anomalous lacrimation is rare but usually associated with Duane syndrome or abduction deficits, as in Möbius sequence and, less frequently, facial nerve palsy. Studies implicate an early insult in development at 4 to 6 weeks. At that time the facial nerve, sixth nerve, and lacrimal nucleus are in close proximity in the embryo.